Late presentation for diagnosis of HIV infection among HIV positive patients in South Tigray Zone, Ethiopia - Admassu Assen; Fantahun Molla; Abrham Wondimu; Solomon Abrha; Wondim Melkam; Ebisa Tadesse; Zewdu Yilma; Tadele Eticha; Hagos Abrha; Birhanu Demeke Workneh (BMC, 2016)
Abstract Background In spite of the availability and accessibility of HIV testing opportunities and efforts, people are being late to test in the course of HIV infection. Late diagnosis leads to late anti-retroviral therapy initiation which in turn results in poor treatment outcome and prognosis of the disease. The aim of this study was to determine the prevalence and predictors of late HIV diagnosis among HIV-infected patients in South Tigray Zone, Ethiopia. Methods A facility based cross sectional study was conducted among HIV positive patients from February 1-30, 2014 in Southern Tigray, Ethiopia. Multistage sampling technique was employed to select the study participants. Data were collected by reviewing patient medical card and interviewing using structured questionnaire. Data were entered using Epi-Data version 3.1 and analyzed using SPSS version 20.0. Both bivariate and multivariate logistic regressions were modeled to evaluate the association of predictors with late diagnosis of HIV infection. Results Out of 789 study participants, 68.8 % of them were late for HIV diagnosis. Feeling healthy (65.7 %), fear of stigma and discrimination (32.4 %) and using traditional treatment (1.5 %) were reported as the main reasons for late HIV diagnosis. Use of Khat [AOR = 3.27, 95 % CI (1.75, 6.13)], bed ridden functional status [AOR = 2.66, 95 % CI (1.60, 4.42)], ambulatory functional status [AOR = 1.56, 95 % CI (1.03, 2.35)] and Muslim religion [AOR = 2.26, 95 % CI (1.13, 4.49)] were significantly associated with late presentation for HIV diagnosis. Conclusions High prevalence of late HIV diagnosis was recorded in Southern Tigray Zone, Ethiopia. Public health educations and campaigns targeted at improving early diagnosis and prognosis of people living with HIV/AIDS in Southern Tigray, Northern Ethiopia should be underway.